2005
DOI: 10.1159/000086144
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Roles of Ectopic Tachygastria Induced with Antral Electrical Stimulation

Abstract: Aim: To investigate the pathophysiological roles of tachygastria using antral electrical stimulation (AES). Methods: The study was performed on 13 healthy female hound-type dogs chronically implanted with three pairs of serosal electrodes and a gastric cannula (n = 7). In the first experiment (n = 7), the antral motility was measured for three 30-min periods right after a solid meal. AES was performed during the second 30-min period at a tachygastric frequency. In the second experiment (n = 6), gastric slow wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Retrograde GES at the tachygastrial frequency is known to induce gastric dysrhythmia and inhibit antral motility (5). Induction of gastric dysrhythmia with retrograde GES was reported to inhibit postprandial antral motility; conceivably, it should also reduce antral tone (46).…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde GES at the tachygastrial frequency is known to induce gastric dysrhythmia and inhibit antral motility (5). Induction of gastric dysrhythmia with retrograde GES was reported to inhibit postprandial antral motility; conceivably, it should also reduce antral tone (46).…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Because of its pacing capability, GES with long pulses is also able to induce tachygastria when delivered at a tachygastrial frequency (a frequency higher than the physiological frequency). 42,43 GES-induced tachygastria was reported to be associated with antral hypomotility, mediated via the adrenergic pathway. 43 …”
Section: Alterations Of Gastric Slow Wavesmentioning
confidence: 99%
“…The other set of parameters was the same as set 1 except for an increase in stimulation frequency to 10 c.p.m., which was called tachygastrial frequency. It has been reported that GES at the tachygastrial frequency using internal serosal electrodes induces tachygastria or tachyarrhythmia 16 …”
Section: Methodsmentioning
confidence: 99%
“…The bag was non‐compliant, 700 mL in maximal capacity and attached to the distal end of a double‐lumen catheter. The catheter was connected to a computer‐controlled electrical barostat device (Distender Series IIR; G & J Electronics, Willowdale, Ontario, Canada) 16 . The bag was briefly inflated with 300 mL air to fully unfold and deflated completely thereafter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation